Process intensification: water electrolysis in a centrifugal acceleration field - Lao, Liyun; Ramshaw, C.; Yeung, Hoi (Springer Science Business Media, 2011)
Intensification of hydrogen production by carrying out water electrolysis in a centrifugal acceleration field has been demonstrated. A prototype single cell rotary water electrolyser was constructed, and a number of design challenges with regard to the practical application were addressed. The rotary electrolyser was tested over a range of current density, centrifugal acceleration, electrolyte concentration, temperature, and electrode geometry. The test results showed that at normal cell operating conditions (7.7M KOH solution, 348K) much of the cell voltage benefits were achieved at an acceleration of about 16g (g=9.81ms-2), equivalent to a rotational speed of 500rpm (revolution per minute) for the rotary cell. The rotary electrolyser cell voltage was about 0.25-0.5V, less than the equivalent static cell under similar operating conditions, depending on the current density. The cell voltages achieved, without an effective electrode catalytic coating, were comparable with typical industrial values of fully developed pressurised cells. At a higher acceleration of 41g, the rotary cell's current density can be up to 13.5kAm-2 without causing gas bubble blinding of the membranes and electrodes. When comparing with typical current densities (about 5kAm-2) found in commercial systems, this study demonstrated the potential of intensification.
Keywords: Centrifugal field; Process intensification; Water electrolysis; Hydrogen production